PERANCANGAN SISTEM INFORMASI KELENGKAPAN CATATAN PERKEMBANGAN PASIEN TERINTEGRASI RAWAT INAP MENGGUNAKAN MICROSOFT VISUAL STUDIO 2010 DI RUMAH SAKIT UMUM PINDAD BANDUNG - Rini Tisnawati; Ajeng Pratiwi (POLITEKNIK PIKSI GANESHA, 2019)
The purpose of this research is to designing of information system inpatients completeness of integrated patient development records using Microsoft Visual Studio 2010 At Rumah Sakit Umum Pindad Bandung. The research method that used in this research is descriptive qualitative approach method. The data collection techniques used are by way of field work practices, study of the literature, interview, and documentation. The development method that used is the waterfall model (Waterfall). Based on the author’s observation during this research, problem which are found : (1) Inputting completeness data performed using a computer still has problems because data inputing is done in Microsoft Excel which has many rows and columns so it is very possible for officers to input data incorrectly. (2) There are still incomplete inpatients integrated patient development records, so that many medical records have been returned to the treatment room, this is due to a lack of thoroughness, busyness and awareness of doctors/other health workers to fill in the medical records, especially inpatients integrated patient development records. The suggestions given to overcome these problems are : (1) Make changes to the system that is running (semi-computerized) by making a designing of information system inpatients completeness of integrated patient development records using Microsoft Visual Studio 2010. (2) socialization and monitoring to health workers in order to always complete filling in integrated patient development record.